The analysis of the charge transport mechanism of n-Si/MEH-PPV device structure using forward bias I-V-T characteristics - Kavasoglu, A. Sertap; Yakuphanoğlu, Fahrettin; Kavasoglu, Nese; Pakma, Osman; Birgi, Ozcan; Oktik, Sener (Elsevier Science Sa, 2010)
In this study, temperature dependent current-voltage (I-V) measurements and investigation of the dc current transport mechanism of n-Si/MEH-PPV device have been performed. While the series resistance value displayed strongly temperature dependent behaviour, the ideality factor varied between 3.2 and 1.8 in the temperature range 110-330 K. The temperature dependent ideality factor behaviour at low temperature region (110-220K) shows that tunnelling enhanced recombination is valid rather than thermionic emission theory and the characteristic tunnelling energy is calculated as 30 meV. There is a slightly linear relationship between the ideality factor and temperature at region II (230-330 K) which is attributed to drift-diffusion current transport in the n-Si/MEH-PPV device as stated already by Osvald. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Schottky diodes; I-V characteristics; Ideality factor; Series resistance; Barrier height; MEH-PPV; Heterojunction diode